2021
DOI: 10.20467/humancaring-d-20-00018
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of In-Service Educational Programs on Nurse Managers' Understanding of the Theory of Technological Competency as Caring in Nursing

Abstract: Healthcare providers in advanced healthcare systems recognize the value of practices involving technological competencies in healthcare. Theory-based practice, grounded in Locsin's Technological Competency as Caring in nursing theory, warrants investments in quality nursing care. This study determined the effect of in-service educational programs for nurse managers regarding perceptions of the theory. Five, 1-hour lecture sessions weekly showed significant effects on understanding technological competency as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that education in TCCN theory improves awareness and understanding of TCCN theory (Nakano et al, 2019(Nakano et al, , 2021. It cannot be denied that the experience of being educated in TCCN theory may affect the results of the survey.…”
Section: Differences Between Perception and Practice Dimensionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have shown that education in TCCN theory improves awareness and understanding of TCCN theory (Nakano et al, 2019(Nakano et al, , 2021. It cannot be denied that the experience of being educated in TCCN theory may affect the results of the survey.…”
Section: Differences Between Perception and Practice Dimensionmentioning
confidence: 96%
“…In addition, his team has developed the Technological Competency as Caring in Nursing Instrument-Revised (TCCNI-R) for use in both the Japanese and English languages. Nakano et al (2019Nakano et al ( , 2021 used the Japanese version of TCCNI-R to investigate the educational effects of TCCN theory on nursing administrators and found that teaching TCCN theory improved nursing administrators' understanding and perception of TCCN theory. Also, Yokotani et al (2021) evaluated the Japanese version of the TCCNI-R by exploratory and confirmatory factor analysis by employing SEM to test for construct validity, and Cronbach's alpha confirmed its reliability.…”
Section: Introductionmentioning
confidence: 99%